Investigation of consumer properties of sweet buns enriched with herbal food additives - M. A. Kazimirova; T. V. Pershakova (Новые технологии, 2017)
Consumer characteristics of a bakery product have been assessed. It’s been established that the developed "Topitam" sweet bun has a higher rating and nutritional value according to organoleptic, physicochemical indicators and safety indicators than the product developed according to the traditional recipe.